Implementation of IOT Automatic Controlling System and Android Franchise System in Oyster Mushroom MSMEs in Gintangan Village To Be Globally Competitive in the Digital Economy Era - Raup Padillah; Fitri Nurmasari; Siti Napisah; Heriberthus Wicaksono (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
MSMEs are one of the business units that play an important role in the growth and development of the economy in Indonesia, especially in lower and middle class society. The MSME